Germline Structural Variations in Cancer Predisposition Genes - Pócza, Tímea; Grolmusz, Vince Kornél; Papp, János; Butz, Henriett; Patócs, Attila; Bozsik, Anikó (Frontiers in Genetics, 2021)
In addition to single nucleotide variations and small-scale indels, structural variations (SVs) also contribute to the genetic diversity of the genome. SVs, such as deletions, duplications, amplifications, or inversions may also affect coding regions of cancer-predisposing genes. These rearrangements may abrogate the open reading frame of these genes or adversely affect their expression, hence can act as germline mutations in hereditary cancer syndromes. With the capacity of disrupting the function of tumor suppressors, structural variations confer increased risk for cancer and account for a remarkable fraction of heritability. The development of sequencing techniques enables the discovery of a constantly growing number of SVs of various types in cancer predisposition genes. Here we provide a comprehensive review of the landscape of germline SV types, detection methods, pathomechanisms, and frequency in cancer predisposition genes, focusing on the two most common cancer syndromes: hereditary breast- and ovarian cancer and gastrointestinal cancers. Current knowledge about the possible molecular mechanisms driving SVs is are also summarized.